FORMULASI BARU JURNALISME LOKAL DALAM MEMPRODUKSI BERITA DI ERA MEDIA SOSIAL - Rivi Handayani (Fakultas Dakwah dan Komunikasi, 2021)
Digital technology has mapped out revolutionary changes in journalism and fundamentally changed the nature and function of media in the public. The explosion of social media and the development of smartphones are causing technology to be the only way to receive factual information quickly. This change gave rise to new players in the domain of digitization of information, which has significantly created uncertain conditions for the future of journalism, especially local journalism. In this context, it is important to adopt the innovations of the social media industry. Based on the analysis, social media provides an opportunity to change the situation by allowing journalists to do three different things in producing news, namely storytelling, multimedia and transmedia. Each category has a different format that local journalism can use in order to survive in digital scenarios without losing its local feel.